2010
DOI: 10.1002/rcm.4333
|View full text |Cite
|
Sign up to set email alerts
|

Under‐reporting of food intake is frequent among Brazilian free‐living older persons: a doubly labelled water study

Abstract: The assessment of food intake is essential for the development of dietetic interventions. Accuracy is low when intake is assessed by questionnaires, the under-reporting of food intake being frequent. Most such studies, however, were performed in developed countries and there is little data about the older population of developing nations. This study aimed to verify the total energy expenditure (TEE) of independent older Brazilians living in an urban area, through the doubly labelled water (DLW) method and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
18
0
2
Order By: Relevance
“…These results are consistent with those obtained in other reviews of dietary records against doubly labeled water held in Brazil [38,39]. Volunteers with a higher body fat percentage tended to under-report more [38]. …”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those obtained in other reviews of dietary records against doubly labeled water held in Brazil [38,39]. Volunteers with a higher body fat percentage tended to under-report more [38]. …”
Section: Discussionsupporting
confidence: 91%
“…Under-reporting of food intake is frequent and has earlier been shown by the doubly labelled water method (Schoeller, 1990;Trabulsi & Schoeller, 2001;Ferriolli et al, 2010). In an earlier review, they found about 25% under-reporting under different conditions.…”
Section: Discussionmentioning
confidence: 98%
“…In dietary assessment, dietary intake is assessed by methods including food record, 24-hour dietary recall, semi-quantitative food frequency questionnaire (FFQ), and dietary history [14][15][16][17][18][19][20][21][22]. The 24hour recall and FFQ are considered to pose less burden on the respondent, but calculation of precise dietary intake is difficult.…”
Section: Discussionmentioning
confidence: 99%